2021
DOI: 10.3389/fphar.2021.577263
|View full text |Cite
|
Sign up to set email alerts
|

Insights Into Patient Variability During Ivacaftor-Lumacaftor Therapy in Cystic Fibrosis

Abstract: Background: The advent of cystic fibrosis transmembrane conductance regulator protein (CFTR) modulators like ivacaftor have revolutionised the treatment of cystic fibrosis (CF). However, due to the plethora of variances in disease manifestations in CF, there are inherent challenges in unified responses under CFTR modulator treatment arising from variability in patient outcomes. The pharmacokinetic (PK) data available for ivacaftor-lumacaftor cystic fibrosis (CF) transmembrane conductance regulator (CFTR) modul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Conversely, the steady state C max for IVA/LUM found in a real-life setting, i.e., outside the stringent frame of clinical trials, was reported to be up to 10 times lower than that of a single-dose level in the labeling information. Moreover, the observed LUM exposure in CF patients was found to correspond to half of that measured in healthy controls (Table S2) [14,26].…”
Section: Pharmacokinetics Of Cftr Modulator Drugsmentioning
confidence: 74%
See 2 more Smart Citations
“…Conversely, the steady state C max for IVA/LUM found in a real-life setting, i.e., outside the stringent frame of clinical trials, was reported to be up to 10 times lower than that of a single-dose level in the labeling information. Moreover, the observed LUM exposure in CF patients was found to correspond to half of that measured in healthy controls (Table S2) [14,26].…”
Section: Pharmacokinetics Of Cftr Modulator Drugsmentioning
confidence: 74%
“…An increase in the AUC of up to four-fold was reported for IVA when taken with fatty meals. Moreover, in their international multicentric clinical PK study, Hanafin et al noticed notable differences in C max values for IVA and LUM in the various participating centers from different continents, but also among neighboring countries, suggesting that the type of food and socio-cultural eating habits might also modulate caftors' PK [14].…”
Section: Pharmacokinetics Of Cftr Modulator Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noteworthy, these studies were conducted with single modulators only and not as the combination therapy used clinically. However, previous work has shown that CFTR modulators can have drug-drug interactions that affect pharmacokinetic properties and hence therapeutic outcomes (Hanafin et al, 2021). Consequently, preclinical prenatal safety studies of concomitant use of combination therapies are urgently needed.…”
Section: Introductionmentioning
confidence: 99%